Wakaf Contribution In The Development of Halal Value Chain Ecosystem On The Legal Perspective In Indonesia - Muthia Eka Destyana; Ro'fah Setyowati (Green Publisher Indonesia, 2022)
The large number of Muslim communities in Indonesia indirectly affects the development of halal lifestyle in Indonesian society. The development of halal lifestyle in Indonesian society is indirectly a potential to further develop the halal value chain ecosystem in Indonesia. The development of the halal value chain ecosystem in this case is not an easy thing in Indonesia, therefore it is necessary to contribute from all parties including the community in the development of the halal value chain ecosystem in Indonesia. The contribution of the community in the development of the halal value chain can actually be in any form, for example in the form of Waqf. This is because Waqf can be one of the instruments to support the development of the halal ecosystem sector because it has the potential and economic benefits that are not only beneficial for the benefit of worship but also for the benefit of the people. So that the contribution of waqf in the development of the halal ecosystem sector is very necessary to note in connection with the pattern of relationships and regulations so that there is no legal dualism in the use of Waqf to develop the halal value chain ecosystem sector in Indonesia